S-adenosylhomocysteine (AdoHcy)-dependent methyltransferase inhibitor DZNep overcomes breast cancer tamoxifen resistance via induction of NSD2 degradation and suppression of NSD2-driven redox homeostasis. (1st February 2020) - Wang, Qianqian; Zheng, Jianwei; Zou, June X.; Xu, Jianzhen; Han, Fanghai; Xiang, Songtao; Liu, Peiqing; Chen, Hong-Wu; Wang, Junjian
Abstract: Endocrine therapies (e.g. tamoxifen and aromatase inhibitors) targeting estrogen action are effective in decreasing mortality of breast cancer. However, their efficacy is limited by intrinsic and acquired resistance. Our previous study demonstrated that overexpression of a histone methyltransferase NSD2 drives tamoxifen resistance in breast cancer cells and that NSD2 is a potential biomarker of tamoxifen resistant breast cancer. Here, we found that DZNep, an indirect inhibitor of histone methyltransferases, potently induces the degradation of NSD2 protein and inhibits the expression of NSD2 target genes (HK2, G6PD, GLUT1 and TIGAR) involved in the pentose phosphate pathway (PPP). DZNep treatment of tamoxifen-resistant breast cancer cells and xenograft tumors also strongly inhibits tumor growth and the cancer cell survival through decreasing cell production of NADPH and glutathione (GSH) and invoking elevated ROS to cause apoptosis. These findings suggest that DZNep-like agents can be developed to target NSD2 histone methyltransferase for effective treatment of tamoxifen-resistant breast cancer. Highlights: DZNep potently induces the degradation of NSD2 protein. DZNep inhibits the expression of NSD2 target genes (HK2, G6PD, GLUT1 and TIGAR) involved in the pentose phosphate pathway. DZNep decreases cell production of NADPH and glutathione (GSH), and elevated ROS. DZNep inhibits TamR breast cancer cell growth in vitro and in vivo .